Efektivitas alat pengontrol porsi makan dalam menurunkan asupan energi dan lemak pada remaja obesitas sentral - Putra, Egy Sunanda; Irfan, Ary; Al Rahmad, Agus; Dahliansyah, Dahliansyah (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Central obesity is one of the major risk factors for degenerative diseases. A health transition is currently occurring, in which central obesity continues to increase in developing countries such as Indonesia. Among adolescents aged >15 years, the prevalence of central obesity rose from 31% in 2018 to 36,8%. Adolescents with central obesity have an 80% likelihood of becoming obese in adulthood and a 75% increased risk of developing diabetes mellitus. The rising prevalence of central obesity in adolescents reflects a dietary shift from traditional diets rich in fruits, vegetables, and whole grains to energy-dense diets high in added sugars, refined carbohydrates, saturated fats, fast foods, and low fiber intake.Objectives: This study aimed to examine the effectiveness of a portion size control on energy and fat intake among adolescents with central obesity.Methods: This study employed a true experimental design with a pre-posttest control group. The study subjects were adolescents aged 16–18 years from senior high schools that provided lunch programs. Participants were selected based on inclusion and exclusion criteria. A total of 106 students were recruited and randomly assigned to either the intervention group (n = 53) or the control group (n = 53). The independent variable was the portion control tool, and the dependent variables were dietary energy and fat intake. Bivariate data analysis was performed using paired t-test for within-group comparisons and independent t-test for between-group comparisons to evaluate the intervention effects.Results: In the intervention group, the portion control tool was effective in reducing energy intake (p = 0,004) and fat intake (p = 0,024). When compared to the control group, the intervention group showed a greater reduction in energy and fat intake (p = 0,028; p = 0,004, respectively).Conclusion: The use of a portion control tool improved energy and fat intake among adolescents with central obesity.